Adopting stunting prevention behaviors: The role of smart posters and family assistance teams (TPK) in Bogor Regency - Satiti, Inten Laras; Wastutiningsih, Sri Peni; Guntoro, Budi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2026)
Introduction: Stunting remains a major public health concern in Indonesia, with prevalence among children under five exceeding 20% in the past decade. To address this, the government established Family Assistance Teams (TPK) and introduced smart posters as educational tools for stunting prevention. This study aims to explore how the role of TPK, together with mothers’ attitudes toward smart posters, shapes their perceived stunting prevention behaviors in Bogor Regency, Indonesia. Methods: A cross-sectional survey was conducted in 2024 among 120 mothers of children under two from nine sub-districts in West, Central, and East Bogor who had received smart posters during pregnancy between 22 November 2022 and 16 April 2023. Participants were selected using convenience sampling. Data were collected using a self-administrated questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test eight hypotheses. Results: PLS-SEM revealed that the role of Family Assistance Teams (TPK) was positively associated with mothers’ attitudes toward smart posters (β=0.42) and directly improved stunting prevention behaviors (β=0.51). Attitudes toward smart posters significantly influenced both stunting knowledge (β=0.51) and behaviors (β=0.21), whereas knowledge itself showed no significant association with behaviors (β= – 0.13). Attitudes fully mediated the effect of TPK on knowledge (β=0.21) and partially mediated its effect on behaviors (β=0.09). The model showed moderate predictive power (R²=0.31; Q²=0.20). The most effective pathway to strengthen stunting prevention behaviors was the direct influence of TPK (β=0.51), further enhanced by positive attitudes toward smart posters as behavioral boosters (β=0.09). Conclusion: The study shows that Family Assistance Teams (TPK) directly improve mothers’ stunting prevention behaviors and foster positive attitudes toward smart posters. These attitudes enhance both knowledge and behaviors, fully the effect of TPK on knowledge and partially mediating its effect on behaviors. The most effective pathway is the direct role of TPK, strengthened by positive attitudes toward smart posters.